2019
DOI: 10.3390/ijerph16214238
|View full text |Cite
|
Sign up to set email alerts
|

Match Performance of Soccer Teams in the Chinese Super League—Effects of Situational and Environmental Factors

Abstract: To investigate the effects of situational factors (match location, strength of team and opponent) and environmental factors (relative air humidity, temperature and air quality index) on the technical and physical match performance of Chinese Soccer Super League teams (CSL). The generalized mixed modelling was employed to determine the effects by using the data of all 240 matches in the season 2015 collected by Amisco Pro®. Increase in the rank difference would increase the number of goal-scoring related, passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 38 publications
4
38
0
1
Order By: Relevance
“…The limited existing evidence on the effects of travel on match activity profile is contradictory in Australian football, where negative effects (Ryan et al, 2017) and no substantial effects (Hiscock et al, 2012) have been reported. Similar inconsistencies in findings on the effects of travel also exist between the studies conducted in other football codes (Lago et al, 2010;Castellano et al, 2011;Kempton and Coutts, 2016;Mitchell et al, 2017;Zhou et al, 2019;Oliva-Lozano et al, 2020). Our findings along with the findings of the only other league-wide study (conducted in the Chinese soccer league) (Zhou et al, 2019) are indicative of the trivial effects of travel on match activity profile on average across a league, or in other words for a typical club.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The limited existing evidence on the effects of travel on match activity profile is contradictory in Australian football, where negative effects (Ryan et al, 2017) and no substantial effects (Hiscock et al, 2012) have been reported. Similar inconsistencies in findings on the effects of travel also exist between the studies conducted in other football codes (Lago et al, 2010;Castellano et al, 2011;Kempton and Coutts, 2016;Mitchell et al, 2017;Zhou et al, 2019;Oliva-Lozano et al, 2020). Our findings along with the findings of the only other league-wide study (conducted in the Chinese soccer league) (Zhou et al, 2019) are indicative of the trivial effects of travel on match activity profile on average across a league, or in other words for a typical club.…”
Section: Discussionsupporting
confidence: 76%
“…Similar inconsistencies in findings on the effects of travel also exist between the studies conducted in other football codes (Lago et al, 2010;Castellano et al, 2011;Kempton and Coutts, 2016;Mitchell et al, 2017;Zhou et al, 2019;Oliva-Lozano et al, 2020). Our findings along with the findings of the only other league-wide study (conducted in the Chinese soccer league) (Zhou et al, 2019) are indicative of the trivial effects of travel on match activity profile on average across a league, or in other words for a typical club. While the negative effects of playing away from home on match outcome is well-established (Pollard, 2006;Lazarus et al, 2017), it has been proposed that tactical, strategic, mental, and officiating factors are responsible, rather than the physical and technical performance of players (Lazarus et al, 2017;Lo et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Analysing the changes in WBGT, it has been observed, that in team sport, players can modulate their activity in high or extreme environmental conditions during the matches, with similar trends as those for temperature and humidity [ 33 , 34 ]. Recently, similar research has been published by Zhou et al [ 35 ], who analysed the physical and technical activity of teams, albeit only in one season of the Chinese super league of football, with a smaller number of climatic conditions and did not take into account the diversity of players in positions.…”
Section: Introductionmentioning
confidence: 90%
“…Game location and match result were included as nominal variables with two levels (home & away, and won & not-won, respectively). The effect of team strength and opponent strength was estimated by including the difference in the log of the end-of-season ranks as a predictor [ 35 , 48 ]. The ground and weather conditions were added as four-level nominal variables (no-wear/low-wear/average-wear/heavy-wear, and sunny/light-rain/heavy-rain/snow, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Hopefully, a large number of papers were published. These high-quality papers covered a wide range of topics in Sports and Health such as different ball games [ 1 , 2 , 3 , 4 , 5 , 6 ], training analyses [ 7 , 8 ], and health aspects such as vitamin D in adolescent athletes [ 9 ], treating obesity and the metabolic syndrome [ 10 , 11 ], infectious diseases such as HIV [ 12 ], exercise addiction [ 13 ], the level of mood and depression [ 14 ], tobacco use in elite athletes [ 15 ], and the aspect of the Covid-19 pandemic [ 16 , 17 ]. We hope that these papers will contribute to the advancement of Sports and Health sciences by offering practical applications for professionals in the field.…”
mentioning
confidence: 99%